Survey Paradigma Masyarakat Yogyakarta Terhadap Keberadaan Serta Konservasi Amfibi dan Reptil - Jayanto, Herdhanu (Badan Pengembangan Konservasi Universitas Negeri Semarang, 2014)
The Special Region of Yogyakarta (DIY) covers an area of 318 590 km2, owns ± 8% of the total number of amphibian and reptile species in Indonesia (± 1.100). Compared to the other groups of animals, these species are relatively easy to find in rural area (remote area). In addition to their high biodiversity value, the existence of these two groups of animals is also an important component of the ecosystem. The analysis of social paradigm in D.I.Y. region aimed to measure the communities’ support towards and knowledge about the conservation of amphibians and reptiles. The survey was conducted in October- December 2013. The Location of the surveys included Gadjah Mada University (Kab. Sleman), Sermo Wildlife (Kab. Progo), Dlingo Village (Kab. Bantul), Kukup Beach and Ngandong (Kab. Gunung Kidul). The data collection was carried out using a questionnaire about amphibians and reptiles. The result showed that most respondents supported the existence of the amphibian and reptile conservation, but the communities’ knowledge was still lacking in order to support the conservation. Law enforcement and legal awareness of some community groups and the publics were still deemed less. On a regional scale, threats to the amphibians and the reptiles were partly antrophogenik and some of them were natural. In addition, on the regional scale, a topic emphasized was the conflict between men and snakes. This study is expected to be basis principles on policy-making, community supporting action and authorities in nature conservation, particularly for amphibians and reptiles.